PEOPLES OF THE EAST CAUCASUS AND ALEXANDER THE GREAT: INTERSECTIONS OF HISTORY, MYTHOLOGY, AND FAITH - Alikberov, Alikber Kalabekovic (History, Archeology and Ethnography of the Caucasus, 2024)
The article explores the intriguing interplay of historical narratives, mythology, and religion in the Eastern Caucasus, with a focus on Alexander the Great (356–323 BC) and the East Caucasian (Nakh-Dagestani) peoples, including the Albanians, Legae, Caspians and others. The study employs a novel multidimensional approach to historical analysis, incorporating the established methodology of histoire croisée, cross-analysis, and an original method of system-logical verification. The earliest historical references to the Caucasian Albanians, dating to the 4th century BC, are exclusively found within the context of Alexander the Great’s conquests. Equally significant are the historical narratives connecting Alexander to the Caspian Gates, the Caspian people, and the “Wall of Iskandar.” The impact of Alexander’s exploits is also evident in mythology, Islamic tradition, and local historiography. The study’s primary findings relate not only to various historical reconstructions but also to an analysis of the remarkable attention given by prominent Eastern Caucasian authors to interpretations of the Quranic story of Dhu al-Qarnayn, the righteous man. The author concludes that the profound interest of Nizami Ganjavi, Abbas-Kuli Bakikhanov, and Hasan Alqadari in events interweaving historical fact with mythological narratives from both Christian and Islamic eschatology is no coincidence. Ancient sources further complicate this narrative by classifying the Albanians, Legae, and Caspians among the indigenous peoples of the Eastern Caucasus, with apparent connections to Caucasian Albania (Aluan/Arran). The discussion of these issues sheds light on the early period of Caucasian history, particularly that of the Nakh-Dagestani peoples, providing vague hints on their probable settlement areas nearly a millennium before the Great Migration Period.
Keywords: Alexander the Great; Dhu al-Qarnayn; Caspian Gate; Iskandar Wall; Albanians; Cadusii; Caspians; Legae; Gelae; Caucasian Albania; Arran